2021
DOI: 10.1016/j.gpb.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the Giant Panda Roundworm Illuminates Its Host Shift and Parasitic Adaptation

Abstract: Baylisascaris schroederi, a roundworm (ascaridoid) parasite specific to the bamboo-feeding giant panda (Ailuropoda melanoleuca), represents a leading cause of mortality in wild giant panda populations. Here, we present a 293-megabase chromosome-level genome assembly of B. schroederi to infer its biology, including host adaptations. Comparative genomics revealed an evolutionary trajectory accompanied by host-shift events in ascaridoid parasite lineages after host separations, suggesting their potential for tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Positive selection was considered the driving force of host adaptation in the parasite genome (Xie et al., 2021). Therefore, we identified the positively selected genes in the S. scabiei genome.…”
Section: Discussionmentioning
confidence: 99%
“…Positive selection was considered the driving force of host adaptation in the parasite genome (Xie et al., 2021). Therefore, we identified the positively selected genes in the S. scabiei genome.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that parasite excretory–secretory (ES) proteins function as bioactive molecules that directly interact with the host immune system. In previous study, we successfully predicted and annotated the secretory proteome by using the whole-genome and transcriptome data of B. schroederi [ 38 ]. At the same time, we found that many of the previously reported proteases and protease inhibitors involved in the parasite–host interaction were also abundant in the secretory proteome of B. schroederi .…”
Section: Discussionmentioning
confidence: 99%
“…20-22 Recently, PDE has also been discovered in other free-living nematodes from Clade V, including other Oscheius species and some Caenorhabditis and Auanema species [Gonzalez de la Rosa, Stevens, Pires-daSilva and Blaxter, personal communications], and Mesorhabditis . 50 Other parasitic nematodes (Clade III Parascaris and Toxocara , 21 Baylisascaris , 51 and Clade IV Strongyloides 52 ) also exhibit DNA break and sequence loss, illustrating the broad phylogenetic distribution of PDE in nematodes. However, other well-studied nematodes, including C. elegans , do not undergo PDE.…”
Section: Discussionmentioning
confidence: 99%